2012
DOI: 10.1055/s-0032-1315012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Foetal Non-invasive ECG instead of Doppler CTG - A Better Alternative?

Abstract: Introduction !In the last 30 years cardiotocography (CTG) has become the most common method to monitor foetal health during birth [1,2].The benefits of electronic foetal monitoring are still discussed [3][4][5]. To solve the problem of high inter-and intra-observer variability [1,[6][7][8], guidelines and computer-assisted analysis pro- Abstract !Introduction: This study aimed to evaluate foetal signal quality obtained using an antenatal foetal ECG system (Monica 24™) and compare it with Doppler ultrasound CTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…, who found that ≥60% of fECG signals were present in 82% of 150 pregnant women. Other studies found antenatal success rates of 62% , 77.4% , and 92.9% , respectively. In the latter studies, recordings were relatively short (up to eight hours), and they were performed in a hospital setting.…”
Section: Discussionmentioning
confidence: 91%
“…, who found that ≥60% of fECG signals were present in 82% of 150 pregnant women. Other studies found antenatal success rates of 62% , 77.4% , and 92.9% , respectively. In the latter studies, recordings were relatively short (up to eight hours), and they were performed in a hospital setting.…”
Section: Discussionmentioning
confidence: 91%
“…Ten of the 43 studies were from the UK [25][26][27]35,[37][38][39]49,50,55], 22 from other European countries [24,[28][29][30][31][32][33]36,40,[42][43][44]48,[51][52][53][54]56,57,61,64,65], five from Japan [41,59,60,62,63], one from India [45], one from Australia [66], three from the United States of America (USA) [46,47,58], and one study from both the Netherlands and USA [34]. The included studies were heterogeneous, they had a median sample size of 34.5 participants (range 1-657) and a median number of recordings of 63 (range 1-657).…”
Section: Resultsmentioning
confidence: 99%
“… Accurate—these methods allow accurate detection of fHR, i.e., Se ≤ 85%, PPV ≤ 95%, ACC ≤ 85%, F1 ≤ 90%. Very Accurate—these methods enable a very accurate determination of fHR and, in this case, it is a full replacement of the conventional CTG [ 31 , 40 , 119 ], i.e., Se ≤ 95%, PPV ≤ 95%, ACC ≤ 95%, F1 ≤ 95%. Morphological analysis (T/QRS; QT)—this parameter classifies the efficacy of the investigated methods from a deeper morphological analysis of fECG.…”
Section: Discussionmentioning
confidence: 99%
“…Very Accurate—these methods enable a very accurate determination of fHR and, in this case, it is a full replacement of the conventional CTG [ 31 , 40 , 119 ], i.e., Se ≤ 95%, PPV ≤ 95%, ACC ≤ 95%, F1 ≤ 95%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation